Characterization of red ballpoint pens using uv-visible spectroscopy and pattern recognition techniques - Razali, Nor Fathin Mohd (Universiti Sains Malaysia, 2015)
One of the important areas in forensic questioned document is the ink analysis. It is performs not to identify the writing implement used to write the document under scrutiny but the ink deposited on the document. Through proper analysis, the ink deposited can be linked to the writing implement used to write the document. In ink analysis, techniques such as Thin Layer Chromatography (TLC), Ultra Violet and Visible (UV-Vis) Spectroscopy and direct visual examination are considered as common. These techniques although have helped to solve crimes involving document, their outcomes are very subjective and depend on the knowledge, skill and most important experience of the examiner. This study purposes the use of chemometrics techniques of principle component analysis (PCA) and hierarchical cluster analysis (HCA) for ink analysis in conjunction with UV-Vis spectroscopy to produce more objective outcomes. In this study, twenty four (24) red ballpoint pen inks from four different brands were analysed using TLC and UVVis spectrometer. The thin layer chromatogram and the UV-Vis spectra obtained from the red ballpoint pen inks were manually examined for features that can be used to successfully differentiate and group the inks according to their brands. The manual examinations proved to be a time consuming and daunting task and more importantly were unable to differentiate the red ballpoint pen inks. On the other hand, PCA and HCA had successfully differentiated and grouped the red ballpoint pen inks according to their brands. The results demonstrated the potential use of PCA and HCA to differentiate and group red ballpoint pen inks of different brands in an objective manner.